Il ritorno dell’Orzeł biały. Memoria, narrazioni e identità polacca attraverso i period e docu-dramas nelle piattaforme di streaming (2011-2022) - Christopher CALEFATI (Diacronie. Studi di Storia Contemporanea, 2022)
Within the consumerist dimension of history, which has seen a remarkable development with the wide propagation of audio-visual materials in streaming platforms, each society produces self-representations that allow the strengthening of certain shared collective values. The complex history of Poland in the 20th century is the subject of large-scale cinema production. The important government intervention in the making of historical films of wide circulation has nourished feelings of national revenge and the crystallization of collective memory. In the fragmentation of identities, the period and docu-Dramas configure a new generational approach by ordinary actors to national discourse in the daily interactions and self-representation of their own history.